Evaluation of deformation and fracture rates for nickel-titanium rotary instruments according to the frequency of clinical use - İşıl Karagöz Küçükay; Rüştü Dağlaroğlu; Sıtkı Selçuk Gökyay; Ayça Yılmaz (Istanbul University, 2018)
DOI: 10.26650/eor.2018.461Purpose To evaluate the deformation and fracture rates for ProTaper Universal (PTU) nickel-titanium rotary instruments according to the frequency of clinical use. Materials and Methods A total of 619 PTU instruments (S1, S2, F1, F2, and F3) that have been used in the clinic by a single endodontist were collected over a period of 4 years. These instruments were grouped on the basis of one to three (Group A), four to six (Group B) and seven to nine (Group C) clinical uses (one canal = one use). All instruments were evaluated by a blinded investigator under a stereomicroscope at 15×-45× magnification for the presence of deformation and fracture. Results The overall rates of deformation and fracture were 10% and 1.2%, respectively. The deformation and fracture rates for the S2, F1, and F2 instruments showed no significant differences among groups. However, fracture rate for S1 instruments in Group A was significantly higher than for those in Group B (p=0.025) and Group C (p=0.004). In Group C, the S1 instruments showed a significantly higher deformation rate compared with the S2 (p=0.04), F1 (p=0.008) and F2 (p=0.049) instruments; there were no other significant differences within groups. Conclusion Under the conditions of the current study, frequency of use seemed to influence the deformation rates of PTU rotary instruments. Except S1, these instruments could be used without any fracture or deformation in up to 9 clinical cases by an experienced endodontist.